How should autonomous vehicles overtake other drivers?. (October 2019) - Ritchie, Owain T.; Watson, Derrick G.; Griffiths, Nathan; Misyak, Jennifer; Chater, Nick; Xu, Zhou; Mouzakitis, Alex
Highlights: Few studies have explored perceptions of specific autonomous vehicle behaviour. Six simulator experiments investigated perceptions of autonomous overtakes. Acceptability of overtakes increased with pull-in distance up to 28 m. Physiological orienting responses were found in response to sharper overtakes. Some influence of traffic context and immersion on perceptions of overtakes. Abstract: Previous research examining trust of autonomous vehicles has largely focused on holistic trust, with little work on evaluation of specific behaviours and interactions with human-controlled vehicles. Six experiments examined the influence of pull-in distance, vehicle perspective (overtaking/being overtaken), following distance and immersion on self-reported evaluations of, and physiological responses to, autonomous motorway overtakes. We found that: (i) overtake manoeuvres were viewed more positively as pull-in distance increased before reaching a plateau at approximately 28 m, (ii) physiological-based orienting responses occurred for the smallest pull-in distances, (iii) participants being overtaken were more forgiving of a sharper pull-in if the overtaking vehicle was followed closely by another vehicle, and (iv) for two of three cross-experiment comparisons participants were more forgiving of smaller pull-in distances with lower immersion levels. Overall, the results suggest that the acceptability of an overtake manoeuvre increases linearly with pull-in distance up to a set point for both overtaking and being overtaken manoeuvres, with some influence of traffic context and levels of immersion. We discuss the findings in terms of implications for the development of assisted and fully autonomous vehicle systems that perform in a way that will be acceptable to both the vehicle occupants and other road users.